2017
DOI: 10.1590/1678-7757-2016-0442
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma fibronectin promotes proliferation and differentiation of odontoblast

Abstract: Objective To assess the effect of fibronectin (Fn) and porcine type I collagen (PCOL) on odontoblast-like cells in vitro.Material and Methods Rat odontoblast-like cells (MDPC-23 cells) were inoculated and cultured on Fn-coated or type I collagen-coated substrates. Proliferation assay, alkaline phosphatase activity (ALP activity), mRNA expression of hard tissue-forming markers, and Alizarin red staining were investigated over a period of 10 days.Results Cells maintained a high proliferation activity on Fn and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…For instance, general protocols for coating cell culture dishes require about 0.1-1 mg/mL of ECM proteins (fibronectin, laminin, Matrigel) to induce better attachment of cells. 20,21 In another study, it was found that a concentration of 3 mg/mL of ECM hydrogel was required to induce gelation in stroke cavities. 22 Thus, in routine studies, where a lot of protein is needed, the use of pure ECM proteins might be an expensive option.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, general protocols for coating cell culture dishes require about 0.1-1 mg/mL of ECM proteins (fibronectin, laminin, Matrigel) to induce better attachment of cells. 20,21 In another study, it was found that a concentration of 3 mg/mL of ECM hydrogel was required to induce gelation in stroke cavities. 22 Thus, in routine studies, where a lot of protein is needed, the use of pure ECM proteins might be an expensive option.…”
Section: Introductionmentioning
confidence: 99%
“…With the passage of time, cells in the other concentration groups also spread, but less rapidly than those in the LN-1 (100 µg/mL) group. Early cell spreading and flattening was observed only in wells coated with 100 µg/mL LN-1, far exceeding the concentration of fibronectin (FN, 10 µg/mL) that is necessary to achieve the same effect (19). These results revealed that LN-1 is less adhesive than FN, as a significantly higher concentration of LN-1 was needed to achieve a comparable degree of cell adhesion.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, we assessed the mRNA expression levels of BSP, ALP and OCN. In an earlier experiment, we had found that BSP was highly responsive to matrix proteins such as type I collagen and FN: coating with these two proteins elicited a dramatic increase of BSP expression (2-3-fold relative to the control) in MDPC-23 cells (19). In contrast, LN-1 coating of polystyrene wells resulted in only modest enhancement of BSP expression (1.15-fold in the LN-1-1 group, 1.29-fold in the LN-1-10 group, and 1.10-fold in the LN-1-100 group).…”
Section: Discussionmentioning
confidence: 94%
“…As main components of the cytoskeleton, these protein structures are known to be very sensitive to any mechanical damage of the cell membrane during cryopreservation. [41] Hence, it is important that the cryopreservation protocol does not cause any disruption in their functionality, particularly resulting from osmotic stresses. [42] Apparently, in our method the random orientation of paper fibers provides protective shield to the cells to withstand the osmotic stresses from the surroundings when they undergo the harsh freezing process.…”
Section: Discussionmentioning
confidence: 99%